Postcolonial camp hybridity and performative inversions in Zsazsa Zaturnnah - Garcia, J. Neil C. (2012)
There is a common presumption that queer theory is global and unproblematically so. This paper argues otherwise, by performing a postcolonial reading of Zsazsa Zaturnah, an extremely popular Philippine "campy" text from 2003, which is easily assimilated into a queer reading that all too devastatingly overlooks its specificities as a postcolonial articulation. In particular, the paper differentiates contemporary Western camp from the postcolonial camp to be found in texts coming from the Global South, whose theories of subjectivity, even if pathetic remain distinct from postmodernism's understanding of agency, simply because they remain entirely utilization in anti colonial and nationalist projects, as this text itself illustrates. Queer theory's doctrine of gender performativity therefore needs to be reinterpreted from the perspective of postcolonial syncretism and/or hybridity, which indeed can be seen to challenge its most basic assumptions regarding the issues of agency and social transformation.
Keywords: Gays in popular culture; Homosexuality; Zsazsa Zaturnnah (Fictional character)